Pengembangan Media Pembelajaran Power Point Interaktif pada Materi Menganalisis Isi Debat Kelas X SMK Negeri 1 Botomuzoi - Dediputrajaya Lahagu; Imansudi Zega (Indo-MathEdu Intellectuals Journal, 2022)
This study aims to determine the effectiveness of interactive powerpoint media on material analyzing the content of class X debate of SMK Negeri 1 Botomuzoi. The method used in this research is research and development. The procedures used in the development process are ADDIE, namely the analysis stage, Design stage, Development stage, Implementation stage, evaluation stage. The subjects that have been determined are students of class X-OTKP SMK Negeri 1 Botomuzoi as well as test subjects for the use of the developed products. The instruments used are validation sheets and questionnaires. The results of data analysis showed that the effectiveness of interactive powerpoint learning media in the material analyzing the content of the debate in class X of SMK Negeri 1 Botomuzoi had been evaluated and obtained a percentage of classical completeness in individual trials reaching 100% with very effective criteria, small group tests reaching 100% very effective criteria, and in field tests reaching 86.7% with very effective criteria so that they were suitable for use in the learning process